Predictors and Outcomes of Salvaging the Corticospinal Tract After Thrombectomy in Basilar Artery Occlusion Stroke - Gwak, Dong-Seok; Choi, WooChan; Kim, Yong-Won; Kang, Dong-Hun; Son, Wonsoo; Hwang, Yang-Ha (Frontiers in Neurology, 2022)
Background Regional eloquence of brainstem structures may contribute to neurological status in basilar artery occlusion (BAO) stroke. The corticospinal tract (CST) which is vulnerable to BAO is important for motor activity. This study investigated the impact of CST salvage on outcomes and its associated factors in patients with BAO treated with thrombectomy. Methods We retrospectively investigated 88 patients with BAO admitted ≤24 h after onset and presented with motor deficits and who underwent thrombectomy. Patients with a pre-stroke modified Rankin Scale (mRS) score of 4–5 who did not undergo baseline brain computed tomography angiography were excluded. CST salvage was evaluated using follow-up imaging (magnetic resonance imaging [MRI] or computed tomography when MRI was not available) after thrombectomy. A good outcome was defined as a 3-month mRS score of ≤2 or 3 if a patient's pre-stroke mRS score was 3. The associations between CST salvage and outcomes and clinical parameters were analyzed using logistic regression analyses. Results Thirty-nine (44.3%) patients had CST salvage and the same number of patients had good outcomes. CST salvage was independently associated with a good outcome [adjusted odds ratio (aOR): 18.52, 95% confidence interval (CI): 4.31–79.67, p < 0.001]. After adjusting for confounders, atrial fibrillation (aOR: 3.92, 95% CI: 1.18–13.00, p = 0.026), location of occlusion (mid-BAO; aOR: 0.21, 95% CI: 0.06–0.72, p = 0.013), length of occlusion (involved segment of BAO <2; aOR: 4.77, 95% CI: 1.30–17.59, p = 0.019), and onset-to-puncture-time ≤180 min (aOR: 4.84, 95% CI: 1.13–20.75, p = 0.034) were significantly associated with CST salvage. Conclusion CST salvage was associated with good functional outcomes in patients with BAO treated with thrombectomy. The presence of atrial fibrillation, location and length of BAO may predict CST salvage after thrombectomy, and rapid treatment with thrombectomy may protect this eloquent tract in these patients.